2009
DOI: 10.1007/s10439-009-9775-1
|View full text |Cite
|
Sign up to set email alerts
|

A Particle Dynamic Model of Red Blood Cell Aggregation Kinetics

Abstract: To elucidate the relationship between microscopic red blood cell (RBC) interactions and macroscopic rheological behavior, we propose a two-dimensional particle model capable of mimicking the main characteristics of RBC aggregation kinetics. The mechanical model of RBCs sheared in Couette flow is based on Newton law. We assumed a hydrodynamic force to move particles, a force to describe aggregation and an elasticity force. The role of molecular mass and concentration of neutral polymers on aggregation [Neu, B.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 30 publications
3
39
0
3
Order By: Relevance
“…Owens [3] derived a microstructure based constitutive equation considering the elastic stress and average aggregate size, which closely agreed with the experimental data from Bureau et al [7], and indicated stress hysteresis with viscoelastic and shear thinning properties. Fenech et al [8] derived a particle-based equation considering the elastic and aggregation forces, which also closely agreed with the experimental data from Bureau et al [7] and model from Owens [3], when comparing the mean average aggregate size of RBCs to the shear rate.…”
Section: Blood Rheologysupporting
confidence: 65%
See 3 more Smart Citations
“…Owens [3] derived a microstructure based constitutive equation considering the elastic stress and average aggregate size, which closely agreed with the experimental data from Bureau et al [7], and indicated stress hysteresis with viscoelastic and shear thinning properties. Fenech et al [8] derived a particle-based equation considering the elastic and aggregation forces, which also closely agreed with the experimental data from Bureau et al [7] and model from Owens [3], when comparing the mean average aggregate size of RBCs to the shear rate.…”
Section: Blood Rheologysupporting
confidence: 65%
“…Constitutive models have since been proposed to model the aggregation and disaggregation of blood [3], [8], which agree with the experimental data from Bureau et al [7]. Owens [3] derived a microstructure based constitutive equation considering the elastic stress and average aggregate size, which closely agreed with the experimental data from Bureau et al [7], and indicated stress hysteresis with viscoelastic and shear thinning properties.…”
Section: Blood Rheologysupporting
confidence: 62%
See 2 more Smart Citations
“…In most previous numerical studies regarding rouleaux formations; 42,84,164 however, simple potential functions were used to compute cell-cell interactions. To accurately predict rouleaux formation, we must solve hydrodynamic interactions between cells more precisely.…”
Section: Hemodynamics In Microvesselsmentioning
confidence: 99%